Sister Stella L. - De Leon, Mike (Regal Films, 1984)
Story of an activist accused of subversion for her involvement in a strike. Her ex-boyfriend journalist?s pro-labor articles are suppressed, strikers are brutally beaten, tortured and salvaged," but Sister Stella L. urges them on with a closing speech full of leftist slogans.